The scarlet shedder - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Dog Man, 2024)
After an encounter with a skunk, Dog Man, now scarlet red after being dunked in tomato juice, is exiled but must find a way to save those who shunned him when an all-new, never-before-seen villain unleashes an army of A.I. robots.